Investigating Mathematical Disposition within Elementary School Mathematics Teaching - Ibad, Nur; Slamet, Mamat (Papanda Publisher, 2023)
This study aims to describe the mathematical dispositions of upper elementary school students within the context of mathematics learning. A qualitative approach with a case study method was employed to explore the characteristics of students’ dispositions in a natural and contextual learning environment. The participants were 62 fifth- and sixth-grade students from SDN Babakan Jawa 1, Majalengka Regency, selected through purposive sampling. The primary instrument was a mathematical disposition questionnaire developed based on seven indicators: self-confidence, flexibility in thinking, perseverance, attentiveness and curiosity, self-monitoring and reflection, appreciation of mathematics in real-life applications, and valuing mathematics in daily life. Data were collected through questionnaires, semi-structured interviews, classroom observations, and documentation, and analyzed through data reduction, display, and conclusion drawing, supported by instrument triangulation. The findings revealed that students generally demonstrated a moderate level of mathematical disposition. The most prominent indicators were attentiveness, curiosity, and appreciation for the practical use of mathematics. In contrast, flexibility in thinking and reflective awareness were relatively weak. These results highlight the need for instructional strategies that foster idea exploration and develop students' metacognitive awareness. Students’ mathematical dispositions were influenced by teaching styles, instructional models, peer support, and the contextual relevance of the material. The study recommends adopting holistic and contextual learning approaches to foster positive mathematical dispositions that support meaningful mathematical learning and problem-solving.